Cranial irradiation significantly reduces beta amyloid plaques in the brain and improves cognition in a murine model of Alzheimer's Disease (AD). Issue 1 (January 2016) - Marples, Brian; McGee, Mackenzie; Callan, Sean; Bowen, Scott E.; Thibodeau, Bryan J.; Michael, Daniel B.; Wilson, George D.; Maddens, Michael E.; Fontanesi, James; Martinez, Alvaro A.
Abstract: Background and purpose: To investigate if cranial X-irradiation reduces amyloid-β (Aβ) plaques and influences cognitive function in a transgenic mouse model of AD. Methods and materials: B6.Cg-Tg (APPswePSEN1dE9)85Dbo/J AD-prone mice were given cranial X-irradiation. The number of Aβ plaques, along with expression of AD specific genes (84 genes: Mouse Alzheimer's Disease RT 2 Profiler™), radiation-associated cytokines (Milliplex® MAP Mouse Cytokine Chemokine Immunoassay) and immunohistochemistry (IL10, IL-1β, Iba1 CD45) was assessed. Behavioral testing was performed to relate changes in Aβ burden to cognitive function using a Morris water-maze task. Results: Single X-ray doses reduced the number ( p  = 0.002) and size ( p  = 0.01) of Aβ plaques. Low-dose fractionation produced greater 50.6% (1 Gy × 10), 72% (2 Gy × 5) and 78% (2 Gy × 10) reductions. Irradiation was associated with gene (Pkp4, 1.5-fold, p  = 0.004) and proteomic (MIP-2, 8-fold, p  = 0.0024) changes at 24–48 h. Microglia increased at 4 weeks post-irradiation ( p  = 0.001). The reduction in Aβ burden (2 Gy × 5) was associated with cognitive improvement ( p  = 0.012). Conclusion: This is the first report that a clinically relevant course of external beam irradiation (2 Gy × 5) produces a significant reduction in AD-associated amyloid-β plaques with a subsequent improvement in cognitive function. However, longer-term studies are needed to define the precise underlying mechanism and longevity of this response.